Larger strength losses and muscle activation deficits in plantar flexors induced by backward downhill in reference to distance-matched forward uphill treadmill walk. Issue 10 (26th November 2018) - Girard, Olivier; Banzet, Sébastien; Koulmann, Nathalie; Chennaoui, Mounir; Drogou, Catherine; Chalabi, Hakim; Racinais, Sébastien
Abstract: We tested the hypothesis that backward downhill walking (eccentric component) impairs both voluntary activation and muscle contractile properties in the plantar flexors and delays recovery as compared to a gradient and distance-matched uphill walk. Fourteen males performed two 30-min walking exercises (velocity: 1 m/ s; grade: 25%; load: 12% of body weight), one downhill (DW) and one uphill (UP), in a counterbalanced order, separated by 6 weeks. Neuromuscular test sessions were performed before, after, 24-, 48- and 72-h post-exercise, including motor nerve stimulations during brief (5 s) and sustained (1 min) maximal isometric voluntary contractions of the plantar flexors. DW (−18.1 ± 11.1%, P < .001), but not UP (−6.0 ± 7.7%, P =.15), decreased torque production during brief contractions for at least three days post-exercise ( P < .05). Voluntary activation during brief contractions decreased after DW ( P < .05), but not UP, and recovered by 24 h. Both UP (−9.3 ± 9.0%, P = .024) and DW (−25.6 ± 10.3%, P < .001) decreased torque production during sustained contractions but voluntary activation ( P = .001) was lower in DW than UP. Peak twitch torque and maximum rates of torque development and relaxation were equally reduced after UP and DW ( P < .05), and recovered by 24 h. DW induced an increase in muscle soreness with peak values observed 48 h post-walking ( P < .001), whereas post-UP exercise changes were non-significant (all P > .05). Using a direct comparison, the capacity to drive the plantar flexors during sustained contractions remains sub-optimal during the three-day recovery period in response to non-exhaustive, downhill backward walking in reference to an uphill exercise matched for distance covered.